2012
DOI: 10.1002/jbt.21417
|View full text |Cite
|
Sign up to set email alerts
|

17β‐Estradiol regulates the expression of antioxidant enzymes in myocardial cells by increasing Nrf2 translocation

Abstract: The transcription factor-E2-related factor 2 (Nrf2) is an important regulator against the process of oxidative stress. It can effectively scavenge oxygen-free radicals within cells to maintain homeostasis. In this study, we cultured primary myocardial cells, established the hypoxia/reoxygenation (H/R) model to simulate myocardial ischemia/reperfusion injury, and examined effects of 17β-estradiol (E2) on the quantitative changes of Nrf2 in cytosolic and nuclear extracts, the mRNA expression of heme oxygenase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
(28 reference statements)
2
23
1
Order By: Relevance
“…Our results on the increased expression of HO-1 gene are in agreement with findings of Yu et al, [7] about E 2 effects of transcription factor Nrf2 on myocardial cells. These authors have shown a concomitant upregulation of the transcription factor Nrf2 in nuclear extracts.…”
Section: Immunohistochemical Analysis Of Dpp III and Ho-1 Localisatiosupporting
confidence: 93%
See 2 more Smart Citations
“…Our results on the increased expression of HO-1 gene are in agreement with findings of Yu et al, [7] about E 2 effects of transcription factor Nrf2 on myocardial cells. These authors have shown a concomitant upregulation of the transcription factor Nrf2 in nuclear extracts.…”
Section: Immunohistochemical Analysis Of Dpp III and Ho-1 Localisatiosupporting
confidence: 93%
“…Increased expression of HO-1 and several other antioxidant enzymes induced in myocardial cells by E 2 treatment was explained by increased nuclear translocation of transcription factor Nrf2 [7]. HO is the rate-limiting enzyme for heme degradation in mammals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen stimulates Nrf2 activation in epithelial cells of the mammary gland, cerebral nerve tissue, primary myocardial cells, umbilical vein endothelial cells, ovarian epithelial carcinoma, and breast cancer cells (Liao et al, 2012;Yu et al, 2012;Zhang et al, 2013b;Gorrini et al, 2014;Meng et al, 2014;Wu et al, 2014). In contrast, estrogen potently inhibits the activities of Nrf2 target proteins (glutathione-S-transferase and quinone reductase), specifically in the uterus, possibly via its liganddependent interaction with Nrf2 (Ansell et al, 2004(Ansell et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…E2 has the potential to protect the liver, small intestine, and kidney against oxidative stress. 3,4) The expression of glutathione Stransferase 5) and superoxide dismutase 6) has been reported to be increased by E2, suggesting a possible antioxidant role mediated by the upregulation of antioxidant enzymes. Glucuronidation of E2 at the 17-hydroxy position is one of the major metabolic pathways, which functionally inactivates E2.…”
mentioning
confidence: 99%